Islamic Education According to Al Rasyidin - Muhammad Rum Sitorus; Usiono Usiono; Azizah Hanum OK (Edumaspul: Jurnal Pendidikan, 2024)
The increasingly rapid development of the times has given rise to problems related to slowness in the development of Islamic studies. One of the factors of this problem is the lack of qualitative and quantitative studies of Islamic educational thought. Therefore, there is a great need for in-depth study and thinking about Islamic education, especially from Muslim intellectual figures whose identities and specific thoughts are rarely highlighted. Therefore, this scientific study aims to examine in more depth the thoughts on Islamic education from the perspective of Prof. Dr. Al Rasyidin, M.Ag. This scientific study uses the Systematic Literature Review (SLR) method with PRISMA analysis. The analysis results stated that Prof. Al Rasyidin has a very in-depth perspective on Islamic education, which refers more to the basic ideas of the conceptualization and practice of Islamic education as exemplified by the Prophet Muhammad. Apart from that, specifically and in-depth, Prof. Al Rasyidin provides a perspective on Islamic education that places more emphasis on the normative dimension.